Innovation and market orientation in smallholder pig production: - Okello, Daniel Micheal Okello; Odongo, Walter; Aliro, Tonny; Owiny, David Okello; Ndyomugyenyi, Elly Kurobuza (Emerald Publishing Limited, 2025)
Purpose – This study aims to assess the relationship between market orientation and innovation while accounting for the use of purchased feeds and access to veterinary services. Design/methodology/approach – This study used primary data collected from a cross-section of smallholder pig farmers in northern Uganda. Data were collected using pre-tested structured questionnaires. Collected data were analyzed in SPSS using descriptive statistics, exploratory factor analysis and hierarchical regression. Findings – Results show that having improved breeds and providing housing to pigs improve system-focused innovation but reduce customer-focused innovation. The use of purchased feeds was associated with higher levels of both dimensions of innovation, while access to veterinary services was only associated with higher levels of system-focused innovation. Customer orientation is positive for both dimensions of innovation, while competitor orientation is positive forsystem-focused innovation, but negative for customer-focused innovation. Lastly, interfunctional innovation was only associated with higher levels of customer-focused innovation. Access to veterinary services and the use of purchased feeds influence the magnitude of the effect of market orientation on innovation. Research limitations/implications – The findings of this paper suggest that improving smallholder pig farmers’ market orientation could lead to a higher level of farm innovation. Similarly, improving access to veterinary services and better feeds could be linked to higher levels of market orientation, as well as farm-level innovation.